Method Validation for Simultaneous Quantification of Olmesartan and Hydrochlorothiazide in Human Plasma Using LC-MS/MS and Its Application Through Bioequivalence Study in Healthy Volunteers - Kumar, Arvind; Dwivedi, Surya Prakash; Prasad, Tulika (Frontiers in Pharmacology, 2019)
A new, simple, sensitive, selective, rapid, and high-throughput liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed and validated for simultaneous quantification of Olmesartan and hydrochlorothiazide in human plasma. Simple liquid–liquid extraction procedure was applied for plasma sample pretreatment using a mixture of diethyl ether and dichloromethane, as an extraction solution. Analytes were separated on UNISOL C18 150*4.6 mm, 5 µm column using methanol, and 2 mM ammonium acetate pH 5.5 (80:20, v/v) as a mobile phase and detected by electrospray ionization in the multiple reaction monitoring (MRM) mode. The mass transition ion pairs were followed in negative ion mode as m/z 445.20 → 148.90 for Olmesartan; m/z 451.40 → 154.30 for Olmesartan D6 and m/z 295.80 → 205.10 for hydrochlorothiazide; m/z 298.90 → 206.30 for hydrochlorothiazide 13C D2. The method showed excellent linearity (r2 > 0.99) over the concentration range of 5.002–2,599.934 ng/ml for Olmesartan and from 3.005 to 499.994 ng/ml for hydrochlorothiazide. Precision (% CV) and accuracy (% bias) for Olmesartan were found in the range of 3.07–9.02% and −5.00–0.00%, respectively. Precision (% CV) and accuracy (% bias) for hydrochlorothiazide were found in the range of 3.32–8.21% and 1.99–3.80%, respectively. This as developed novel and high-throughput liquid–liquid extraction bioanalytical method has substantial innovative value with the benefits of cost effectiveness, good extraction efficiency, shorter analysis run time, low organic solvent consumption, and simpler procedure over the previously reported solid-phase extraction method. The application of this method in pharmacokinetic studies was further demonstrated successfully through a bioequivalence study conducted on healthy human subjects, following oral administration of combined formulation of Olmesartan medoxomil and hydrochlorothiazide in fixed-dose tablet.